Socialization of the Role of Packaging and Design in Product Marketing at PT ABC: Sosialisasi Peran Kemasan dan Desain Terhadap Pemasaran Produk di PT ABC - Vania Tiara Salsabila; Riski Ayu Anggreini (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
Packaging is the main factor that can increase consumer appeal. Food product packaging is not only a marketing tool to attract buyers' attention, but also to maintain and protect the safety of food products from the danger of contamination. PT ABC's product packaging design still does not attract the attention of buyers, making the product unable to compete with other products on the market. This problem can be overcome by providing outreach to human resources (HR) employees about the importance of packaging and design. In addition, plans for changes to the product packaging design and plans for improving the primary packaging are provided to ensure product safety. The result of this activity is that PT ABC's human resources employees know the importance of packaging and design for products, especially for black tea bags, and get ideas for improving packaging design and primary packaging that can be used on products.